Calcium affects CHP1 and CHP2 conformation and their interaction with sodium/proton exchanger 1. Issue 2 (7th January 2020) - Liang, Shuo; Fuchs, Simon; Mymrikov, Evgeny V.; Stulz, Anja; Kaiser, Michael; Heerklotz, Heiko; Hunte, Carola
Abstract: Calcineurin B homologous proteins (CHPs) belong to the EF‐hand Ca 2+ ‐binding protein (EFCaBP) family. They have multiple important functions including the regulation of the Na + /H + exchanger 1 (NHE1). The human isoforms CHP1 and CHP2 share high sequence similarity, but have distinct expression profiles with CHP2 levels for instance increased in malignant cells. These CHPs bind Ca 2+ with high affinity. Biochemical data indicated that Ca 2+ can regulate their functions. Experimental evidence for Ca 2+ ‐modulated structural changes was lacking. With a newly established fluorescent probe hydrophobicity (FPH) assay, we detected Ca 2+ ‐induced conformational changes in both CHPs. These changes are in line with an opening of their hydrophobic pocket that binds the CHP‐binding region (CBD) of NHE1. Whereas the pocket is closed in the absence of Ca 2+ in CHP2, it is still accessible for the dye in CHP1. Both CHPs interacted with CBD in the presence and absence of Ca 2+ . Isothermal titration calorimetry (ITC) analysis revealed high binding affinity for both CHPs to CBD with equilibrium dissociation constants ( K D s) in the nanomolar range. The K D for CHP1:CBD was not affected by Ca 2+, whereas Ca 2+ ‐depletion increased the K D 7‐fold for CHP2:CBD showing a decreased affinity. The data indicate an isoform specific regulatory interaction of CHP1 and CHP2 with NHE1.